The Wonderful World of Queer Cinephilia - Ghosh, Shohini (BioScope: South Asian Screen Studies, 2010)
The silence around queerness is decisively broken. Much has happened in the last two decades. Today, there are queer groups, writers, activists, academics, filmmakers, and an increasing number of spaces where friendship, solidarity, and political engagement can be nurtured. Queer activism has been responsible for bringing a legal challenge to Section 377 (IPC) that criminalizes “sexual acts against the order of nature”.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Créateur.rice LGBTQ+; _Nettoyé